Seeing Technology Through Five Phases: A theoretical framing to articulate holism, ethics and critique in, and for, technological literacy - Keirl, Steve (Design and Technology Education: An International Journal, 2009)
This article presents a tentative framing that has emerged out of one person’s theorised and reflective professional practice with pre-service primary and secondary Design and Technology teachers as well as with practising teachers, school leadership teams and curriculum policy designers and writers. Over many years, several curricular and pedagogical challenges have presented themselves and, in part, the framing is an attempt to address such challenges. However, the framing principally engages with the major challenge of helping ‘make the invisible visible’. That is, given the pervasiveness and complexity of the phenomenon of Technology (big ‘T’), is there a way of helping ‘see’ it more easily? It is hoped that this theoretical framing might be a valid contribution the development of ethical technological literacy. Critical commentary is sought.